Identification of environmental impacts on the installation of a wind farm (Revista LIDER, 2019)
This article analyzes the environmental aspects and impacts in the installation of wind farms located in Rio Grande do Norte, Brazil. It is part of a master's research in conclusion. Summarize the results of an environmental assessment and evaluation of environmental aspects and impacts, performed during installation of wind farms, as a condition for environmental licensing. Through a basic technical tool for identification and analysis of environmental aspects and impacts, Listing Control, there was the main aspects and presentas impacts on park facility. Also a comparison between the main aspects and impacts of installing a hydroelectric, thermal and wind presenting the main impacts inherent in the installation of enterprises.